Engineering Interactive Systems: EIS 2007 Joint Working Conferences, EHCI 2007, DSV-IS 2007, HCSE 2007, Salamanca, Spain, March 22-24, 2007 : Selected Papers - Hutchison, David; Kanade, Takeo; Kittler, Josef; Veer, Gerrit C. van der; Wesson, Janet (Lecture Notes in Computer Science, 2008)
Engineering Interactive Systems 2007 is an IFIP working conference that brings together researchers and practitioners interested in strengthening the scientific foun- tions of user interface design, examining the relationship between software engine- ing (SE) and human-computer interaction (HCI) and on how user-centerd design (UCD) could be strengthened as an essential part of the software engineering process. Engineering Interactive Systems 2007 was created by merging three conferences: * HCSE 2007 - Human-Centerd Software Engineering held for the first time. The HCSE Working Conference is a multidisciplinary conference entirely dedicated to advancing the basic science and theory of human-centerd software systems engineering. It is organized by IFIP WG 13.2 on Methodologies for User-Centerd Systems Design. * EHCI 2007 - Engineering Human Computer Interaction was held for the tenth time. EHCI aims to investigate the nature, concepts, and construction of user interfaces for software systems. It is organized by IFIP WG 13.4/2.7 on User Interface Engineering. * DSV-IS 2007 - Design, Specification and Verification of Interactive Systems was held for the 13th time. DSV-IS provides a forum where researchers wo- ing on model-based techniques and tools for the design and development of - teractive systems can come together with practitioners and with those working on HCI models and theories.